Methods and models for assessing energy resources first IIASA Conference on Energy Resources, May 20-21, 1975 - Grenon, Michel (IIASA proceedings series, 1979)
Methods and Models for Assessing Energy Resources covers the proceedings of the First IIASA Conference on Energy Resources, held on May 20-21, 1975. This book mainly focuses on energy resources, such as coal, oil and natural gas, and uranium resources, and the assessment of these resources. This text first discusses general activities and classification of energy resources, including the institutions involved, problems faced, and opportunities. This book then explains the methods for assessing petroleum resources. This text devotes two parts, each explaining two energy resources-coal and uranium. This book concludes by explaining the need to further the research and study of this subject. This publication will be invaluable to students and experts in the field of chemistry, particularly engaged in the study of energy resources. Sectors and industries mainly dependent on energy resources will also find this book of significance.--Provided by publisher.